Media and democracy between propaganda and incitement - Jaeed, Hameed (ALBAHITH ALALAMI, 2020)
First: The entrance to media and democracy The growth of the media and the development of its technologies are linked to the development of the democratic system and its political and mass institutions. In many cases, the technologies concerned were able to open the closed doors to the spread of democracy and broaden the base of its applications. As Dupre points out, “audio-visual has opened the image and sound after printing has opened the natural language” (1) to democratization. The generalization of the book, due to the development of printing, led to the transcendence of the Church’s dominance in Europe, and the direct broadcasting and transmission of information enabled the media to transcend the domination of factional systems. On top of that and that, the development of media technologies has opened the coffers of human and social memory for the purpose of possessing knowledge, and how to translate it into a continuous daily action. It allowed us to see the shape of the earth, see the weather conditions and economic movement, see the political decision directly, and get to know better the data of the scientific and technical achievement (2).